Feasibility of a community-based Functional Power Training program for older adults - Tan QLL (Dove Medical Press, 2018)
Queenie Lin Ling Tan,1 Lilian Min Yen Chye,1 Daniella Hui Min Ng,1 Mei Sian Chong,1 Tze Pin Ng,1,2 Shiou Liang Wee1,3 1Frailty Research Program, Geriatric Education and Research Institute (GERI), Singapore; 2Department of Psychological Medicine, National University of Singapore, Singapore; 3Faculty of Health and Social Sciences, Singapore Institute of Technology, Singapore Purpose: Community-based programs can increase and sustain physical activity participation in older adults, even for those who are physically frail. We studied the feasibility and potential effect of a 12-week structured Functional Power Training (FPT) program involving high velocities and low loads for older adults conducted in a common area of their housing estate.Patients and methods: The structured FPT program was conducted in collaboration with a health promotion social enterprise and a community service provider based in a public housing site. We recruited nine inactive residents as participants to the single, group-based, twice-weekly program. Attendance and adverse event(s) were recorded throughout the program. The Short Physical Performance Battery, Timed Up and Go (TUG), and 30s Sit-to-Stand tests were used to assess functional outcomes pre- and postprogram. The FRAIL Scale was used to assess their frailty status, and a postprogram experience survey was conducted.Results: Eight subjects (aged 74±10 years) completed the program with an average overall attendance of 90.3%, with at least five participants present for each session. Changes in functional outcomes showed a moderate-to-large effect with significant improvement in TUG (p<0.01). In addition, participants either reversed or maintained their frailty status (p<0.01). Overall, the program was perceived to be well structured, engaging, as well as providing physical and psychosocial benefits. No exercise-related adverse events occurred during the program, and participants were keen to recommend this program to others.Conclusion: Community-based structured FPT is safe and feasible for frail older adults, with the potential to improve function and reverse frailty status. Keywords: multicomponent exercise, frail older adults, functional performance, community-based program